2016
DOI: 10.1016/j.redox.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Redox balance influences differentiation status of neuroblastoma in the presence of all-trans retinoic acid

Abstract: Neuroblastoma is the most common extra-cranial solid tumor in childhood; and patients in stage IV of the disease have a high propensity for tumor recurrence. Retinoid therapy has been utilized as a means to induce differentiation of tumor cells and to inhibit relapse. In this study, the expression of a common neuronal differentiation marker [neurofilament M (NF-M)] in human SK-N-SH neuroblastoma cells treated with 10 μM all-trans retinoic acid (ATRA) showed significantly increased expression in accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Additionally, a significant suppression of the expression of antioxidant genes, such as SOD and CAT, was detected in AgNP-exposed cells, while they were significantly upregulated in RA-treated cells. The link between RA and the upregulation of SOD2 has also been reported previously [ 77 , 78 ]. Collectively, the results suggest that the mitochondria may be involved in AgNP-induced ROS generation, as consistent with previous reports showing the role of the mitochondria in AgNP-induced ROS generation [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, a significant suppression of the expression of antioxidant genes, such as SOD and CAT, was detected in AgNP-exposed cells, while they were significantly upregulated in RA-treated cells. The link between RA and the upregulation of SOD2 has also been reported previously [ 77 , 78 ]. Collectively, the results suggest that the mitochondria may be involved in AgNP-induced ROS generation, as consistent with previous reports showing the role of the mitochondria in AgNP-induced ROS generation [ 79 , 80 ].…”
Section: Discussionsupporting
confidence: 75%
“…Our findings corroborated with earlier finding suggest that decreased catalase activity is associated with increased differentiation of human neuroblastoma cell line (IMR-32) [ 64 ]. Upon the treatment with ATRA, the level of anti-oxidant markers including GSH, (GPx), and catalase levels were significantly decreased following ATRA treatment compared to untreated group in several time points in human SK-N-SH neuroblastoma cells [ 65 , 66 ]. Recently, Dayem et al reported that moderate level ROS induced by AgNPs seems to be important factor for differentiation in SH-SY5Y cells [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, ROS can act as signaling molecules in neuronal cells too, for instance, as far as the differentiation activity of retinoic acid is concerned 4–6 . Thus, the ability to balance oxidative insults is crucial for neuronal cell survival.…”
Section: Introductionmentioning
confidence: 99%